Foreignization and domestication strategies in cultural term translation of tourism brochures - Choirul Fuadi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2016)
In translating brochure, a translator has to make a decision on the basis of the message and purpose. The translator is faced by two strategies of translation – foreignization and domestication. The purpose of the study is to examine how the interrelationship between cultural term translation and foreignization or domestication strategy in the cultural term translation of tourism brochure from Indonesian into English. This study used qualitative descriptive with discourse analysis strategy. The note-taking technique is used to identify and classify the data. The objects of the study are tourism brochures from Province of Special Region of Yogyakarta and Central Java in 2015. The findings show that the translation strategies used depend on the translation process. When the cultural terms are familiar, translator tends to use domestication strategy and consider the target text. Translator chooses domestication strategy because try to make tourist understand the text and produce communicative and natural translation. On the other hand, when cultural terms are foreign, translator using foreignization strategy and consider source text. Using foreignization strategy, translator tends to introduce traditional cultural term.